Universalisme Paulus Menurut Alain Badiou: Uraian dan Tantangan - Yasintus T. Runesi (Reformed Center for Religion and Society, 2016)
ABSTRACT: When people believe that social particularities raise plurality of views in the contemporary society, Badiou introduces the idea of the universality of the singular subject with the aim of overcoming the so-called global village without solidarity. This article is a description of Badious thought, which is included in the line of thinkers which moves